Pancasila Dan Keindonesiaan Tarik Menarik Pemaknaan dan Perwujudan Pancasila - Hamdan Zoelva (Universitas Nasional, 2020)
Amid the atmosphere of the PSBB because of the threat of Covid19 public were surprised by the decision of the meeting Parpurna house of representatives passed the draft law on the Bow of the Ideology of Pancasila (RUU HIP), as the initiative RUU of the house of representatives. The response of the audience was crowded, and happens resistance from various parties, not only from the Islamic but also from other circles. Pull understanding of Pancasila and its manifestations in the life of the country is commonplace occur in the stage of post-constitutional (lower stage). One of them is the fact that the religion of Islam as the power of the majority nation, Indonesia is the objective conditions that can not be ignored in any policy of the state, that proved to be the doctrine and Islamic law continues to transform in a variety of forms of state policy. Throughout the process of constitutional democracy are respected and become the cornerstone in the life of the state because of the influence of Islamic values in the embodiment of Pancasila on the policy of the state, then the system will continue to take place.